Identification of active substances in pear paste for the treatment of cough in mice using spectrum-effect relationship study - Min Xu; Yuhui Yu; Huixin Xu; Meiqing Li (Journal of Functional Foods)
In this study, the researchers produced a pear paste using typical Dangshan pear fruits. The mechanism that enables the paste to treat cough and related inflammatory responses was systematically investigated using an ammonia-induced mice cough model. The pear paste and its polar extracts relieved cough symptoms, as evidenced by 44.0%, 53.4%, and 47.2% decreases in cough frequency and 21.0%, 43.3%, and 53.4% increases in latent period for pear paste, ethyl acetate extract (EAE) and n-butanol extract (WBE), respectively. In addition, the paste and its polar extracts reduced lung injuries, including alveolar dilatation, alveolar wall damage, and airway thickening. The two polar extracts exhibited anti-inflammatory effects in the airway through the suppression of a Th1 cytokine (IFN-γ, significantly suppressed by 15.49% and 16.33% for EAE and WBE, separately). A spectrum-effect relationship analysis was conducted to identify arbutin, protocatechuic acid, chlorogenic acid and naringin as the primary bioactive substances contributing to the antitussive and anti-inflammatory activities of pear paste.